ETHNOMATHEMATICS: THE CONCEPT OF WEIGHTED GRAPHS IN THE TRADITIONAL GAME OF DAM - Bustan, Ariestha Widyastuty; Mahmud, Rauman; Gafur, Anuwar Kadil A; Salmin, Munazat (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2024)
This research integrates graph theory concepts with the traditional game of DAM originating from North Maluku, particularly in Ternate City. An ethnomathematics approach is employed to bridge mathematics education with the preservation of local culture. The DAM game is represented as a weighted graph, where game stones serve as vertices, and the lines connecting the stones represent edges with weights corresponding to the number of steps between stones. Using ethnographic methods, the study observes the rules, strategies, and mathematical aspects of the DAM game. Findings reveal that strategies for capturing opponent stones can be represented as vertex deletion and edge addition in the graph. Additionally, the shortest path with minimum weight in the weighted graph is used to determine optimal strategies for players to reach the opponent's first row. This research enriches mathematics education through cultural approaches while supporting the preservation of traditional games as local cultural heritage